The accuracy of determining newborn’s maturity between New Ballard’s score, Ballard’s score, and first day of last menstrual period - Ferdy Limawal; Djauhariah A. Madjid; Dasril Daud (Paediatrica Indonesiana, 2008)
Background Developing country such as Indonesia needs a toolto assess gestational age which is simple, practical, cheap, fast,and accurate. In 1991 the Ballard maturation score was refinedand expanded to achieve greater accuracy and called New Ballardscore.Objective The purpose of this study was to determine thecorrelation between gestational age assessed by New Ballard score,Ballard score, and by the first day of last menstrual period (LMP).Methods A cross sectional study has been carried out in Dr.Wahidin Sudirohusodo, Ibnu Sina, Labuang Baji, and St. FatimahHospitals in Makassar, from July 1 st , 2006 until January 31 st , 2007.This study included healthy newborns, aged 15 minutes to 24hours born to mothers who knew with certainty the first day oftheir LMP. Diagnostic test was used to analyze the data.Results There were 248 subjects included in this study. The resultsshowed that there was a strong correlation between gestationalage by LMP and New Ballard score (r=0.97), LMP and Ballardscore (r=0.95), as well as between New Ballard score and Ballardscore (r=0.99). New Ballard score was more accurate and had ahigher association coefficient (k=0.85) than did Ballard score(k=0.82) to LMP in identifying premature baby. The sensitivityof New Ballard score to identify premature baby was 87.7%,specificity 96.3%, positive predictive value 95.2% and negativepredictive value 90.2 %.Conclusions New Ballard score can be used to replace Ballardscore if LMP can not be assessed. Further study needs to be donewith bigger sample, involving other paramedics and unhealthynewborn babies.